Misaligned shoulders - Silva, Íris Santos; Correia, Aníbal; Santos, Rita; Aleixo, Catarina; Santos, Mafalda (BIRTH AND GROWTH MEDICAL JOURNAL, 2021)
Sprengel deformity is a congenital elevation of the scapula. Herein is reported the case of a child with the right scapula at a higher level compared to the left and limited abduction of the right shoulder. Other pathoanatomical anomalies can be associated. Treatment is usually conservative, since surgery is only considered in patients with severe scapular function limitation, neck pain, or to improve cosmesis.